Emissões de poluentes em centrais hidrelétricas: aspectos técnicos, econômicos e ecológicos - Siqueira, Ricardo Barbosa Posch [UNESP] (2015)
The reservoir of the hydropower plants contributes to increased emissions of greenhouse gases (GHG), emitting carbon dioxide (CO2) and methane (CH4), that are harmful gases to the global warming. This work aims to develop a methodology that assess the hydroelectric powerplants on the environmental aspect and its ecological efficiency. Analyze the hydroelectric to the ecological efficiency considers the pollution indicator to determine how polluter is a process of electricity generation. Initially, used a reservoir model where consider the operating system of the plant, correlating it to the variable volume, flooding area, water quality and load of the reservoir. The methodology is based on the static / computational model using a software tool (Excel®) and considering a reservoir whose characteristic of the section and volume are related to a trapezoidal plane figure. The study considers the characteristics of the hydroelectrics Itaipu and Tucuruí, which can be obtained the average emissions of CO2 and CH4. The equations are developed to tC and tCO2 equivalent emissions, which support in the development and validation of the model and of the environmental impact study, and in the determination of the hydropower ecological efficiency. Those equations are written as a function of the reservoir load and water quality index, that considers dissolved oxygen saturated (ODSat%). To determine the load of reservoir is considered an electrical analogy (Resistor-Capacitor Circuit), where the reservoir is equivalent to a capacitor and the turbine equivalent to electrical resistance. In the environmental analysis, it is used the equivalent emission of CO2 (tCO2eq) to determine the pollution indicators and the ecological efficiency of the hydroelectric plant, including the Global Warming Potential (GWP). Concludes with the developed model that the ... (Complete abstract click electronic access below)